Organocatálise assimétrica e sistemas vinílogos: adição de 1,3-oxazolina-2-tionas a aldeídos a,b-insaturados - Matsuo, Bianca Taeko (2017)
The use of organic molecules in stereoselective transformations has emerged as a powerful tool for the efficient construction of chiral skeletons and complementing existing methods. Currently, a great variety of reactions using organocatalytic methods (Diels-Alder and cycloadditions in general, Mannich and Michael aldol reactions, epoxidation, α-halogenation, amination, among others) has been developed for the formation of new C-C bonds, being important for the continuous advances of this field of asymmetric catalysis the application of new methodologies, catalysts and substrates. In this work, we explored the reactivity of 1,3-oxazoline-2-thiones scaffolds as Michael donors in organocatalyzed conjugated reactions to a,b-unsaturated aldehydes. By using the Jørgensen organocatalyst it was possible to obtain the functionalized heterocyclic compounds in high yield with ee up to 99% and 9:1 d.r.